Morphology and morphometry of infra orbital foramen in South Indian adult dry skulls - K Vishal; K V Vinay; I P Johncy (Wolters Kluwer Medknow Publications, 2014)
Background: The infra orbital foramen (IOF) situated below infra-orbital margin (IOM) transmits infraorbital nerve and infra- orbital vessels. The knowledge of the dimension, shape and direction of the IOF has important implications in various surgical and anaesthetic procedures. This will avoid iatrogenic injury to neurovascular bundle emerging from the IOF. Material and methods: Sixty adult dry skulls of unknown sex from the Department of Anatomy and Department of Forensic Medicine were used. IOF on both sides of skulls were assessed for the shape and direction by inspection. The vertical and horizontal diameter of the IOF was measured using a digital Vernier caliper to the nearest millimeters and the results were statistically analyzed. Results: The shape of the IOF was vertically oval in majority of the skulls (37.5%) and was semi lunar shaped in 10.83% of the skull. The IOF was directed infero- medially in about 52.5% of the cases and was directed medially in 6.67% of the cases. The mean transverse diameter was 2.96mm and the mean vertical diameter was 3.7mm. All the above results were compared with studies of previous workers. Conclusion: The present study confirms that there is racial as well as regional variation in the shape and dimensions of IOF, thus emphasizing the need to have morphometric data for South Indian population.